The role of the railways in the future of air transport - Givoni, M (ScienceGuide, 2008)
Policy makers support substitution of aircraft services by High Speed Train (HST) services, mainly due to growing congestion at major airports and the skies between them and the potential for environmental benefits. This substitution is usually promoted through competition between the modalities.